2010
DOI: 10.1007/s00240-010-0314-1
|View full text |Cite
|
Sign up to set email alerts
|

Kidney displacement in complete supine PCNL is lower than prone PCNL

Abstract: To compare the amount of the kidney displacement in the complete supine percutaneous nephrolithotripsy (PCNL) to the prone PCNL during getting renal access. Thirty-three patients were randomly divided into two groups. The patients in group A were placed in the complete supine position and the patients in group B in the prone position. Amounts of the kidney displacement in three states and other data were analyzed. The mean amount of the kidney displacement in the complete supine PCNL was 10.1 ± 7.9 mm in stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…No patient in either group developed severe sepsis. The slightly better outcome in the supine PCNL group for complications is probably explained by the easy and straightforward puncture leading to less bleeding and renal damage during tract dilatation and manipulation [19] . There were no cases of adjacent visceral injury in either group, whilst Duty et al [20] reported a lower risk of visceral injury in the supine position.…”
Section: Discussionmentioning
confidence: 93%
“…No patient in either group developed severe sepsis. The slightly better outcome in the supine PCNL group for complications is probably explained by the easy and straightforward puncture leading to less bleeding and renal damage during tract dilatation and manipulation [19] . There were no cases of adjacent visceral injury in either group, whilst Duty et al [20] reported a lower risk of visceral injury in the supine position.…”
Section: Discussionmentioning
confidence: 93%
“…They found that the amount of kidney displacement was 10.1 ± 7.9, 10.7 ± 8.28 and 12.2 ± 10.4 mm in the supine group at the indicated time points, significantly lower than that in the prone group with the value being 16.6 ± 5.8, 16.2 ± 6.3 and 17.6 ± 6.7 mm, respectively. It was suggested in their study that supine PCNL possessed advantages over the prone PCNL such as safety, effectiveness and less occurrence of kidney displacement (5). Zhong et al in China also reported that supine PCNL helped monitor the anaesthesia state and could be smoothly completed in most cases with satisfactory outcome achieved (6).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Falahatkar et al [26] showed more kidney displacement when access is gained in prone position compared with supine position. Gaining access proved to be more difficult with greater kidney displacement.…”
Section: Key Pointsmentioning
confidence: 97%